Effects of fuels, engine load and exhaust after-treatment on diesel engine SVOC emissions and development of SVOC profiles for receptor modeling. (February 2015) - Huang, Lei; Bohac, Stanislav V.; Chernyak, Sergei M.; Batterman, Stuart A.
Abstract: Diesel exhaust emissions contain numerous semivolatile organic compounds (SVOCs) for which emission information is limited, especially for idling conditions, new fuels and the new after-treatment systems. This study investigates exhaust emissions of particulate matter (PM), polycyclic aromatic hydrocarbons (PAHs), nitro-PAHs (NPAHs), and sterane and hopane petroleum biomarkers from a heavy-duty (6.4 L) diesel engine at various loads (idle, 600 and 900 kPa BMEP), with three types of fuel (ultra-low sulfur diesel or ULSD, Swedish low aromatic diesel, and neat soybean biodiesel), and with and without a diesel oxidation catalyst (DOC) and diesel particulate filter (DPF). Swedish diesel and biodiesel reduced emissions of PM2.5, Σ15 PAHs, Σ11 NPAHs, Σ5 Hopanes and Σ6 Steranes, and biodiesel resulted in the larger reductions. However, idling emissions increased for benzo[k]fluoranthene (Swedish diesel), 5-nitroacenaphthene (biodiesel) and PM2.5 (biodiesel), a significant result given the attention to exposures from idling vehicles and the toxicity of high-molecular-weight PAHs and NPAHs. The DOC + DPF combination reduced PM2.5 and SVOC emissions during DPF loading (>99% reduction) and DPF regeneration (83–99%). The toxicity of diesel exhaust, in terms of the estimated carcinogenic risk, was greatly reduced using Swedish diesel, biodiesel fuels and the DOC + DPF. PAH profiles showed high abundances of three and four ring compounds as well as naphthalene; NPAH profiles were dominated by nitronaphthalenes, 1-nitropyrene and 9-nitroanthracene. Both the emission rate and the composition of diesel exhaust depended strongly on fuel type, engine load and after-treatment system. The emissions data and chemical profiles presented are relevant to the development of emission inventories and exposure and risk assessments. Highlights: Emissions of PM and 36 SVOCs are measured in exhaust from a heavy-duty diesel engine. Three engine conditions, three fuels and two after-treatment systems are tested. Under load, PM and SVOC emissions using biodiesel and low aromatic diesel are reduced. While idling, PM and 5-nitroacenaphthene emissions increase with biodiesel. DOC + DPF after-treatment is highly effective in reducing PM and SVOC emissions.